Avaliação de alterações moleculares em pacientes com Câncer Colorretal (CCR) e aplicabilidade na técnica de Biópsia Líquida - Bianca Gomes Fernandes (2022)
Colorectal cancer (CRC) is one of the leading causes of morbidity and mortality worldwide. Detection prior to metastasis and ppropriate therapeutic application lead to greater patient survival and quality of life. However, the diagnosis and postoperative surveillance are surrounded by limitations, which contribute to the high computed mortality. The detection of genetic biomarkers and their better applicability in practice are influential factors that contribute to favorable clinical outcomes. To better understand the molecular basis associated with colorectal cancer, we investigated KRAS, NRAS, BRAF, EGFR and TP53 genes in the DNA of tumor and healthy cells using Sanger sequencing. The most frequent alteration, present only in the tumor DNA (somatic), was used to investigate, by Digital PCR (ddPCR), the detection and analysis of circulating tumor DNA (ctDNA) in the plasma. Altogether, 42 subjects made up the study, most of them male (59.5%), with a mean age of 63 years (SD: 10.0; min: 41; max: 83) and tumors located in the right colon ( 21.4%). transversal (2.4%), left (4.8%), sigmoid (33.3%) and straight (38.1%). Germline and somatic allelic variants were found in the KRAS, EGFR and TP53 genes. The most frequent somatic alteration in the study was rs121913529, which showed a statistically significant association with alcohol consumption (p = 0.002). Also involving somatic alterations, it was observed that patients with a somatic mutation in TP53 are ten times more likely to die, compared with the chance of those without a mutation in this tumor suppressor gene (OR 11.2; 95% CI 1.25 - 245). The applicability of these somatic changes in the liquid biopsy technique was demonstrated by the positivity of rs121913529 in plasma ctDNA by ddPCR. Therefore, the results obtained expand the understanding of the molecular basis of CRC and present an optimization of the liquid biopsy technique, timely for clinical practice.